SMEs Role in Achieving Sustainable Development - Tonis (Bucea-Manea), Rocsana (Journal of Economic Development, Environment and People, 2015)
Sustainable development might be achieved by entrepreneurial enterprises with social responsibility, by innovative SMEs leaded by innopreneurs that not only respect the 21 Agenda advices, but innovate in technologies that reduce the impact of ecological footprint, or that might regenerate natural resources. It is also well know that “the cost of protecting the environment without polluting it is cheaper than bringing a contaminated environment back to its old one. As a result clean and nature-friendly technologies are preferred, and yet again, if there still any pollutants they have to be recycled”. [Kendirli, 2014] We always return to the principium “primun non nocere”. The article is a plea for accomplishing de sustainable development principles, and shows how SMEs may foster it.